Assessing Activities, Participation, and Quality of Life in Hemophilia: Relevance, Current Limitations, and Possible Options - David, Judy Ann; Feldman, Brian M. (Seminars in Thrombosis and Hemostasis, 2015)
The international classification of functioning (ICF) has provided a basic framework for the measurement of outcomes in any health condition. This includes the assessment of the level of activity, participation, and the quality of life of an individual with hemophilia. The measure of activity is an assessment of the individual's ability to perform daily tasks while participation assesses the social role of the individual. The health-related quality of life is an assessment of the perception of the individual's physical, mental, and social well-being. These functional outcomes are important to understand the impact of the broad spectrum of interventions in the management of hemophilia. The generic instruments used to measure these may be less sensitive than the disease-specific measures but are useful for the comparison between cohorts with different health conditions. Cross-cultural validity is essential for tools where the question can vary in the context of different cultures.
Keywords: outcome assessment; activity; participation; quality of life